Songwriting : methods, techniques and clinical applications for music therapy clinicians, educators and students - Baker, Felicity, 1970-; Wigram, Tony (Jessica Kingsley Publishers, 2005)
This comprehensive and groundbreaking book describes the effective use of songwriting in music therapy with a variety of client populations, from children with cancer and adolescents in secondary school to people with traumatic brain injury and mental health problems. The authors explain the specific considerations to bear in mind when working with particular client groups to achieve the best clinical outcomes. All the contributors are experienced music therapy clinicians and researchers. They provide many case examples from clinical practice to illustrate the therapeutic methods being used, together with notated examples of songs produced in therapy. Particular emphasis is placed on how lyrics and music are created, including the theoretical approaches underpinning this process. This practical book will prove indispensable to students, clinical therapists, music therapists, educators, teachers and musicians.